Pengaruh Kepercayaan Kepada Pemerintah, Norma Sosial, dan Sanksi Perpajakan terhadap Perilaku Kepatuhan Pajak - Miftah Imanda Sari; Eka Fauzihardani (Universitas Negeri Padang, 2024)
This study intends to investigate trust government, social norms, and tax penalties affect tax compliance behavior. Primary data are utilized in this form of research. primary data collected from respondents' responses to questionnaires. 399 individual taxpayers from the city of Padang—both employers and employees—served as the study's sample. The statistical data analysis technique used in this study is multiple regression analysis. The study's conclusions indicate that while trust in the government and tax penalties have a positive effect on tax compliance behavior, societal norms have no bearing on it. The Tax Service Office must take action to establish a favorable environment, according to the research's implication. There is an increase in trust in the government enforced by the tax authorities, and there are more sanctions, for example, when outreach to taxpayers is done to encourage taxpayers to abide by tax regulations that have been decided by the government. Taxes are imposed on taxpayers in order to force them to fulfill the required tax responsibilities.